PENERAPAN METODE PROJECT BASED LEARNING “TEMAN JEPANG” MELALUI PENGGUNAAN APLIKASI HELLOTALK UNTUK PEMBELAJARAN MENULIS BAHASA JEPANG - Dhevi Amalia Hermawan; Miftachul Amri (Undiksha Press, 2022)
This study aims to describe the application of the “Teman Jepang” project-based learning method through the use of the HelloTalk application for learning to write Japanese and to find out how the students respond after the implementation of the “Teman Jepang” project-based learning method through the use of the HelloTalk application. The method used is a qualitative descriptive method with the primary data collection process through a study of documents and field data, as well as the results of student response questionnaires. The subjects of this study were 196 students from class XII MIPA and class XII Language at SMA Negeri 10 Malang. The results of the data analysis showed that the interest of students in the application of the